Analytical performance of the Albumin Cobalt Binding (ACB®) test on the Cobas MIRA® Plus analyzer - Gidenne, Stéphane; Ceppa, Franck; Fontan, Eleonore; Perrier, Françoise; Burnat, Pascal (Clinical chemistry and laboratory medicine, 2004)
Recently a new biological marker, Ischemia Modified Albumin (IMA®), measured by the Albumin Cobalt Binding (ACB®) test, was introduced for detection of myocardial ischemia. During ischemia, the metal binding capacity of albumin for certain transition metals like cobalt is reduced. The precise mechanism of action for producing IMA is not known but appears to be related to the production of reactive oxygen species that modify the metal binding sites. The ACB test is a quantitative assay that detects IMA by measuring the cobalt binding capacity of albumin in human serum. We evaluated the analytical characteristics of the ACB test, and reagent and specimen stability, using the Cobas MIRA® Plus instrument. Coefficients of variation for within-run and between-run assays were <4%. No significant interference was observed for concentrations of triglycerides and hemoglobin up to 7 mmol/l and 3.8 g/l, respectively. No interference was apparent with bilirubin. Measures from paired samples of heparinized plasma and serum were not equivalent. The assay is validated for commercial use with serum, therefore our study reported results for serum specimens only. All assays were completed within 5 hours after blood withdrawal. The one-sided upper 95th percentile, calculated for the ACB test in 150 healthy subjects, was 87.00 U/ml. There was no observed difference between men and women or with age. We conclude that the ACB test adapted on the Cobas MIRA Plus analyzer is satisfactory, but strict attention to sample handling procedures is necessary to maintain stability of the analyte.